Preserving Serat Centhini’s Culinary Tradition for Tourism Gastronomic by Mbak Denok’s Grilled Chicken: Pelestarian Tradisi Kuliner Serat Centhini untuk Pariwisata oleh Ayam Panggang Mbak Denok Karanganyar - Purnaningsih, Sri (RADIANT: Journal of Applied, Social, and Education Studies, 2024)
Traditional culinary delights have a long history and deep meaning on the Indonesian culinary map. The purpose of this research is to find out the culinary position of grilled chicken in Serat Centhini, to know aspects of preservation and development aspects in Mbak Denok’s grilled chicken. This study uses qualitative research with the type of case study research. The research location was carried out in Jatipuro District, Karanganyar Regency. To obtain data, this study applies several methods, namely: interview, observation, literature, documentation, and interview methods. After going through the research process, the following conclusions were obtained. The position of traditional culinary roast chicken is a traditional culinary, listed in the Serat Centini as a complement to offerings at certain traditional ceremonies, mentioned 9 times in Serat Centini in volume II and volume VI and is consumed by the King and his family. The preservation of traditional grilled chicken culinary takes place at Ms. Denok's roast chicken, Jatipuro on the aspect of the main raw material in the form of using local free-range chicken, aspects of spices that are still fresh from the local area, aspects of cooking tools using kuali, aspects of cooking methods by roasting using kuali and baked goods firewood and a traditional kitchen in the form of pawons.